Ուշագրավ դիտարկում ԺԹ. դարի հայերի մասին - Հովհաննիսյան, Հայկազ («Նաիրի» հրատ.)
A document kept in the Archive Department of Matenadaran (Archive of the Lazarevs, fund 108, file 96) is an article published in the newspaper Raduga (Rainbow, January, 1860). It is written in Russian and entitled “Statistical and Ethnographic Information about the Armenians in Turkey, Russia, and Other Countries.” The author provides important statistical information about the number of Armenians in the world and makes many noteworthy historical and ethnographic observations about them. The article also contains notes of other Russian authors about the Armenian nation. Хранящийся в Матенадаране (архив Лазаревых, фонд 108, дело 96), документ – статья, опубликованная в январском номере газеты “Радуга” за 1860 год, написана на русском языке и озаглавлена “Статистические и этнографические сведения об армянах в Турции, России и других странах”. В статье рассматриваются важные статистические сведения о численности армян в мире и многие заслуживающие внимания исторические и этнографические наблюдения об армянах. В статье приведены также наблюдения других русских авторов об армянском народе.
Keywords: Հայոց պատմություն; Աղբյուրագիտություն